Torsion of ovary and acute abdomen - Saurabh, Suvidha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian torsion refers to partial or complete rotation of ovarian vascular pedicle. This study explored the presenting symptoms and management of ovarian torsion in a newly established ESIC Medical College and Hospital, Bihta, Patna. This report presents two cases of ovarian torsion, the presenting symptoms and management. This underscores the need of prompt diagnosis and management to improve postoperative outcomes.